Imobilização de co-porfirinas catiônicas em sílica-gel de potencial interesse para modelo biomimético dos citocromos P450 - Lins, Francisco César Costa (2020)
Cobalt metalloporphyrins (CoPs) are compounds widely studied as oxidation catalysts and biomimetic models of cytochrome P450. In this work, the ortho and para isomers of cobalt(III) N-methylpyridylporphyrins were synthesized, characterized, and immobilized on non-functionalized chromatographic silica gel. Initially, the corresponding precursor N-pyridylporphyrins were obtained, which were alkylated with methyl tosylate resulting in the cationic porphyrins meso-tetrakis(N-methylpyridinium-X-yl)porphyrin chloride, H2TM-X-PyPCl4 (X = 2, 4). Finally, the complexes of Co(III), meso-tetrakis(N-methylpyridinium-X-yl)porphyrinatocobalt(III) chloride, CoTM-X-PyPCl5 (X = 2, 4), were obtained by metallation of the corresponding H2TM-X-PyPCl4 (X = 2, 4) with cobalt(II) acetate in aerobic medium. Free base porphyrins and CoPs were characterized by thin layer chromatography (TLC) and UV-VIS spectroscopy, the data being consistent with those reported in the literature. CoPs were also analyzed by thermogravimetric analysis (TGA), revealing three regions of mass loss, but the attribution of mass losses was not conclusive and further studies are needed. The immobilization of cationic CoPs on chromatographic silica gel by electrostatic interaction was carried out under reflux in water for 3 h. The loading of CoPs in the materials was 3.35 μmol g–1 for SiO2/CoTM-2-PyPCl5 and 3.21 μmol g–1 for SiO2/CoTM-4-PyPCl5. The solids were characterized by diffuse reflectance UV-VIS spectroscopy, confirming the immobilization of CoPs. Despite the routes for the synthesis of CoPs and for the preparation of the immobilized materials have been established in this work, further studies to assess the purity of compounds and isolated materials are still needed.